PELUANG BISNIS DAN POTENSI BISNIS BAKED POTATO DENGAN BRAND LOKAL YANG KOMPETITIF - Widarma, Mikael Alvin; Vidyarto Nugroho (Jurnal Serina Abdimas, 2024)
The growing culinary industry in Indonesia presents significant opportunities for baked potato businesses with competitive local brands. Initially popular in Western countries, baked potatoes are now gaining traction in Indonesia as a healthier and more innovative alternative to fast food. This study aims to analyze the opportunities and potential of the baked potato business in Indonesia through product adaptation strategies that align with local tastes, the use of high-quality ingredients, and creative marketing. The research methods include market research, consumer preference analysis, and studies on digital marketing strategies and business operations. The findings indicate that flexibility in topping variations and product differentiation provide a competitive edge for this business, especially with the growing trend of healthy lifestyles among consumers. Strong branding strategies, product innovation, and efficient operational management are key factors in the success of a baked potato business with a local brand in Indonesia's culinary market. ABSTRAK. Industri kuliner Indonesia yang terus berkembang membuka peluang besar bagi bisnis baked potato dengan brand lokal yang kompetitif. Baked potato, yang awalnya populer di negara-negara Barat, kini mulai digemari di Indonesia sebagai alternatif makanan cepat saji yang lebih sehat dan inovatif. Penelitian ini bertujuan untuk menganalisis peluang dan potensi bisnis baked potato di Indonesia melalui strategi adaptasi produk sesuai selera lokal, penggunaan bahan-bahan berkualitas, serta pemasaran kreatif. Metode penelitian meliputi riset pasar, analisis preferensi konsumen, serta studi terhadap strategi pemasaran digital dan operasional bisnis. Hasil penelitian menunjukkan bahwa fleksibilitas variasi topping dan diferensiasi produk memberikan keunggulan kompetitif bagi bisnis ini, terutama dengan meningkatnya tren gaya hidup sehat di kalangan konsumen. Strategi branding yang kuat, inovasi produk, serta manajemen operasional yang efisien menjadi faktor utama dalam keberhasilan bisnis baked potato dengan brand lokal di pasar kuliner Indonesia.